Osiadanie Powierzchni Półprzestrzeni Konsolidującej Pod Działaniem Obciążenia Statycznego - Z. Kończak (Engineering Transactions, 1973)
In the paper is considered the case of plane strain of the skeleton of a consolidating halfspace loaded by a tangential force at the surface. The considerations are based on the linear theory of flow of a liquid through porous, deformable media, as formulated by M. A. Biot. As a result of the solution of the linear consolidation theory, the formula is derived which determines the setting of the surface of a consolidation halfspace as a function of time. The solution is compared with the solution of an analogous boundary value problem of elasticity. The solution derived corresponds to a unit load and constitutes a Green function; thus it may be used to the construction of solutions in the cases of arbitrary, also time-dependent, loading of the surface.